2018
DOI: 10.14710/jgi.6.2.76-81
|View full text |Cite
|
Sign up to set email alerts
|

Gangguan siklus menstruasi kaitannya dengan asupan zat gizi pada remaja vegetarian

Abstract: Background : Adolescence is a period that is still experiencing growth, especially the reproductive system with menstruation is supported adequate nutrients. Objective : The aim of this study was to determined  the association of the sufficient of protein, vitamin B12, vitamin C, iron intake, nutritional status with cycle mestruasi on vegetarian adolescent at IVS Jakarta 2017. Method : This design research was observation analytic with cross sectional approach. Sampling technique were used total sampling. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
1
5
1
6
Order By: Relevance
“…This results are different from research conducted by Wahyuni and Dewi (2018) in Semarang, where the results showed that the mean of body fat precentage in women with menstrual disorders was lower than in women with normal menstrual cycles, which was 22.46±4.8% in women with menstrual cycle disorders and 24.30±3.6% in women whose menstrual cycles are normal, because the majority of respondents in the study were in normal BMI (10).…”
Section: Variablecontrasting
confidence: 99%
See 1 more Smart Citation
“…This results are different from research conducted by Wahyuni and Dewi (2018) in Semarang, where the results showed that the mean of body fat precentage in women with menstrual disorders was lower than in women with normal menstrual cycles, which was 22.46±4.8% in women with menstrual cycle disorders and 24.30±3.6% in women whose menstrual cycles are normal, because the majority of respondents in the study were in normal BMI (10).…”
Section: Variablecontrasting
confidence: 99%
“…Wahyuni and Dewi (2018) found different results in a study at Semarang, they showed that macronutrient intake except protein in women with normal menstruation was higher than women with menstrual cycle disorders because people in Semarang usually consumed low fat diets (10). Food patterns are influenced by two factors, external factors and internal factors.…”
Section: General Description Of Respondentsmentioning
confidence: 99%
“…11 Penelitian oleh Dewi dan Wahyuni pada remaja vegetarian dikemukakan ada 35,71% remaja mengalami gangguan siklus menstruasi oligomenore dan bahwa asupan protein yang tercukupi dapat memaksimalkan fase folikuler. 12 Sementara dalam penelitian oleh Khairiyah pada mahasisiwa fakultas kedokteran dan ilmu kesehatan di Jakarta dikemukakan mahasiswa memiliki kebiasaan makan yang tidak sesuai pedoman gizi seimbang dan terjadi karena adanya ketidakteraturan pola makan saat melaksanakan kegiatan perkuliahan. 13 Berdasarkan uraian dan data tersebut, peneliti tertarik untuk melakukan penelitian tentang hubungan asupan makronutrien dengan gangguan siklus menstruasi pada mahasiswi Fakultas Kedokteran Universitas Nusa Cendana Kupang karena melihat dari padatnya aktivitas perkuliahan di Fakultas Kedokteran, berpengaruh pada perhatian mahasiswi terhadap pola makan dan asupan gizi yang dikonsumsi yang turut memengaruhi kesehatan reproduksinya.…”
Section: Pendahuluanunclassified
“…Pasalnya, semakin banyak penumpukan lemak dalam tubuh, tubuh jadi makin kebingungan untuk mengatur produksi hormon estrogen, akhirnya jumlah hormon tersebut menjadi tidak normal 8 .Beberapa orang responden juga mengakui bahwa mereka jarang mengkonsumsi buah dan sayur, sehingga mereka kekurangan vitamin C. Kekuranganvitamin C dapat menghambat proses absorpsi besi, padahal absorpsi besi yang efektif dan efisien memerlukan suasana asam dan adanya reduktor, seperti vitamin C.Vitamin C dapat menghambat pembentukan hemosiderin yang diimobilisasi untuk membebaskan besi jika diperlukan. Vitamin C juga memiliki peran dalam pemindahan besi dari transferin di dalam plasma ke feritin hati 9 .Asupan gizi yang tidak ade kuat menyebabkan ketidakteraturan menstruasi pada kebanyakan remaja putri. Pada status gizi lebih (overweight dan obesity) biasanya mengalami anovulatory chronic atau menstruasi tidak teratur secara kronis.…”
Section: Pembahasanunclassified